Language, modernity and the politics of identity: geographical perspectives and prescriptions - Summerby-Murray, Robert E. (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 2000)
Over the last two decades geographers and linguists have begun to analyse language as a social determinant of place. While there are numerous traditional studies of regional vocabulary and linguistic geographies, few of these studies have moved towards a perspective of language as a key element of a cultural politics of resistance. This paper argues that language offers both a means of resistance and a method of cultural recovery for regions and communities facing increasing marginalisation at the end of the millennium. As a means of reviewing the role of language as a mechanism of place creation, status distinction and political resistance, this paper offers a case study of Westcock, New Brunswick, that highlights the role of language variation in the shaping of a politics of identity.